Heritability and phenotypic correlation of characters related to grain yield and morphology of canola - Krüger, Cleusa Adriane Menegassi Bianchi; da Silva, José Antonio Gonzales; Medeiros, Sandro Luís Petter; Dalmago, Genei Antonio; Gaviraghi, Juliano (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to estimate the heritability and to evaluate the phenotypic correlations of canola (Brassica napus) traits related to grain yield components and plant architecture. Three experiments were carried out using 0.20, 0.40 and 0.60 m row spacing. During two crop years (2008 and 2009), the genotypes 'Hyola 432' and 'Hyola 61' were evaluated at plant densities of 20, 40, 60 and 80 plants per square meter in each experiment. A complete block experimental design was used in a 2x2x4 factorial arrangement (years x genotypes x densities), with four replicates. Evaluations were done for components linked to production (grain yield per area and per plant, number of pods per plant, number of grains per pod and per plant, and pod mass), and to the morphology of canola (pod length, number of secondary branches, height of insertion of the secondary branch, branch length and number of tertiary branches). Grain yield per area and per plant have higher heritability in the narrower row spacing. The number of pods and of seeds per plant are the components with higher direct and positive correlation with yield.